Health-Promoting Lifestyle and Its Related Factors in Pregnant Women: A Comprehensive Review - Komail Wasel Alamer et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Pregnancy is a critical period that requires women to adopt health-promoting behaviors to ensure optimal maternal and fetal health. A health-promoting lifestyle includes proper nutrition, regular physical activity, stress management, and adequate prenatal care. Various factors, such as socioeconomic status, education level, social support, and access to healthcare, influence the adoption of such behaviors. This review examines the components of a health-promoting lifestyle during pregnancy, the factors influencing these behaviors, and the implications for improving maternal and neonatal outcomes. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/275 https://doi.org/10.5281/zenodo.14480785